Effects of Polyphenols Extracted from Tamarind (Tamarindus indica L.) Seed Coat on Body Weight, White Blood Cells, Bursa of Fabricius and NDV-HI Titer of Broilers under Chronic Heat Stress - Srikhun, T.; Aengwanich , W.; Kongbuntad, W. (International Journal of Poultry Science, 2010)
The purpose of this experiment was to investigate the effects of polyphenols extracted from tamarind (Tamarindus indica L.) seed coat on total body weight, white blood cells, bursa of Fabricius and NDV-HI titer of broilers maintained in high environmental temperature. The broilers under study were divided into two main groups. Those in the first group were maintained at 26"2oC and the second group at 38"2oC. The broilers in the second group were subdivided into six sub-groups, each of which received polyphenols at 0, 100, 200, 300, 400 and 500 mg/kg in their diets. The results revealed that the body weights of the broilers in all groups were not different. The total white blood cell counts and lymphocyte counts of the broilers in all sub-groups of the second group were higher than that of the broilers in the first group (p<0.05). On day 21 of the experimental period, the total number of white blood cells and lymphocytes of the broilers in the first group was not different from those of the broilers in the first, second, fifth and sixth sub-groups of the second group (p>0.05). The relative bursa of Fabricius weight of the broilers in the first group and the third sub-group of the second group were not different (p>0.05). Furthermore, lesion scores of the bursa of Fabricius of the first group and the third and fourth sub-groups of the second group were not different (p>0.05). Moreover, NDV-HI titer of the broilers in the first group and all sub-groups of the second group were not also different (p>0.05). These phenomena indicated that polyphenols could increase the number of lymphocytes and relative bursa of Fabricius weight. On the other hand, the extract could decrease lesion scores of bursa of Fabricius in heat stressed broilers.